2010
DOI: 10.1186/1743-422x-7-107
|View full text |Cite
|
Sign up to set email alerts
|

Proteome changes of lungs artificially infected with H-PRRSV and N-PRRSV by two-dimensional fluorescence difference gel electrophoresis

Abstract: BackgroundPorcine reproductive and respiratory syndrome with PRRS virus (PRRSV) infection, which causes significant economic losses annually, is one of the most economically important diseases affecting swine industry worldwide. In 2006 and 2007, a large-scale outbreak of highly pathogenic porcine reproductive and respiratory syndrome (PRRS) happened in China and Vietnam. However little data is available on global host response to PRRSV infection at the protein level, and similar approaches looking at mRNA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…Our study showed that HSPB1 in PAM cells was up- and down-regulated by the virulent HuN4 strain and the attenuated HuN4-F112 strain, respectively, which confirmed related previous studies [18] , [20] . In addition, infections involving many other viruses, such as the avian influenza H9N2 [38] , the Epstein-Barr virus [39] , the African swine fever virus [40] , IBDV [41] and CSFV [42] also induce upregulation of HSP27 expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that HSPB1 in PAM cells was up- and down-regulated by the virulent HuN4 strain and the attenuated HuN4-F112 strain, respectively, which confirmed related previous studies [18] , [20] . In addition, infections involving many other viruses, such as the avian influenza H9N2 [38] , the Epstein-Barr virus [39] , the African swine fever virus [40] , IBDV [41] and CSFV [42] also induce upregulation of HSP27 expression.…”
Section: Discussionsupporting
confidence: 92%
“…Ding et al [19] utilized the JL/07/SW strain (HP-PRRSV) to infect PAM cells in vitro and detected 29 differentially expressed proteins. Xiao et al [20] identified 45 differentially expressed proteins using the virulent Chinese strain and the attenuated North American strain to infect pigs in vivo and then compared the proteomic changes induced by the virulent/attenuated strain in lung tissue. However, the specific proteins involved in viral replication in these infections remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This dataset can also be compared to other proteomic approaches that have been applied to the study of PRRSV interactions with the host cell and virus particles, which include changes in the abundance of proteins involved in translation . To our knowledge, this is the first application of SILAC coupled to GFP‐Trap pull‐downs for the analysis of a viral protein and mapping an interactome.…”
Section: Proteins Identified In the N‐egfp Trap And Differentiated Frmentioning
confidence: 99%
“…A recent study from Xiao et al compared the proteome patterns of lung samples taken from pigs infected with either a highly virulent Chinese strain of PRRSV, a less virulent North American strain, or with no infection, using 2D-DIGE. Also these authors found mainly changes in the central metabolic pathways, and found very few strain specific changes, but including however the observation that different types of heat shock proteins were up regulated as a response to these two different strains of PRRSV [103]. In a more recent study these authors also presented a genome wide transcriptome analysis of the host response to the North American strain, using deep-sequencing technology which provides the so far most sensitive detection of gene regulation possible [104].…”
Section: Porcine Lung Pathogensmentioning
confidence: 94%